Ocorrência de anticorpos Anti-leptospira spp. em mamíferos silvestres da região metropolitana de Campinas, aglomerado urbano de Jundiaí e Unidade Regional Bragantina, estado de São Paulo - PAULINO, Jéssica da Silva (2020)
The objective was to verify the occurrence of anti-Leptospira spp. antibodies in free-living wild mammals in the regions of the Campinas Metropolitan Region - RMC (20 municipalities), Jundiaí Urban Agglomerate - AUJ (seven municipalities), and Bragantina Regional Unit - URB (11 municipalities), State of São Paulo, Brazil. For this purpose, 267 blood serum samples from 26 species, 17 families and eight orders (Carnivora, Cetartiodactyla, Cingulata, Didelphimorphia, Lagomorpha, Pilosa, Primates and Rodentia) were used. In order to obtain more samples (n=62), the mammals were restrained according to the specific protocol for each species. The blood serum were was examined by the Microscopic Agglutination Test (MAT) with a collection of 24 live leptospiral antigens from the following serogroups and serological variants: Australis (Australis and Bratislava), Autumnalis (Autumnalis and Butembo), Batavia (Bataviae), Ballum (Castellonis), Canicola, Celledoni (Whitcombi), Cynopteri, Djasiman (Sentot), Grippotyphosa, Hebdomadis, Icterohaemorrhagiae (Copenhageni and Icterohaemorrhagiae), Javanica, Panama, Pomona (Pomona), Pyrogenes, Sejroe (Guaicura, Harjo and Hardjobovis), Shermani, and Tarassovi. The sera were screened at a 1: 100 dilution (cut off), and those with 50% or more agglutination were titrated in a series of geometric dilutions of ratio two. Among the examined sera, 11 (4.1%) were seropositive for anti-Leptospira spp. antibodies. In total, there were 11 seropositive mammals: three crab-eating fox (Cerdocyous thous), two maned wolves (Chrysocyon brachyurus), two brown brocket (Mazama gouazoubira), an orange-spined hairy dwarf porcupine (Sphiggurus villosus), a capybara (Hydrochoerus hydrochaeris), a white-eared opossum (Didelphis albiventris) and a black-tufted marmoset (Callithrix penicillata). The detected serovars according to the analyzed species were: crab-eating fox (Pomona), maned wolf (Australis and Icterohaemorrhagiae), orange-spined hairy dwarf porcupine (Autumnalis), capybara (Panama), brown brocket (Panama and Canicola), white-eared opossum (Sejroe) and black-tufted marmoset (Autumnalis). Considering the region, the seropositive mammals from RMC came from the municipalities of Itatiba and Pedreira, AUJ from Jundiaí and Louveira and URB from Atibaia and Bragança Paulista. This research represented the first serological survey of leptospirosis in these three geographic regions of the State of São Paulo.